IMF Research Bulletin, March 2005. (IMF Research Bulletin; IMF Research Bulletin ;, 2005)
The IMF Research Bulletin, a quarterly publication, selectively summarizes research and analytical work done by various departments at the IMF, and also provides a listing of research documents and other research-related activities, including conferences and seminars. The Bulletin is intended to serve as a summary guide to research done at the IMF on various topics, and to provide a better perspective on the analytical underpinnings of the IMF's operational work.